気候変動がアジアパシフィック域の水産養殖業に与える影響 - 吉松, 隆夫; YOSHIMATSU, Takao (三重大学, 2015)
application/pdf 世界規模での気候変動が水産養殖業の営みに与える影響に対する詳細な科学的調査とその影響緩和への対策の素早い実施が必要とされている。本研究では，応募者がこれまで実施してきた様々な国際協力事業で得た世界各地の研究者のネットワークを活用し，アジアパシフィック域の各地における養殖業をいくつかのケースパターンに分け，それぞれに与える気候変動の影響の共通性や相違点を，共通の評価軸を基に明らかにした。そして調査と予備的な実験で得られた結果から，養殖業の持続的発展のためには，今後どのような調査や集中的研究が必要かを提言として纏め，その具体的対策を新たなプロジェクトとして開始する材料を得た。 Recently negative impacts caused by global warming on aquaculture are spotlighted. In recent years some abnormal weather events caused by human-induced global warming like extremely strong storms and heavy rain falls threat aquaculture activities as well. As aquaculture highly depends on local natural resources and conditions the impacts caused by global warming is direct and significant. Also the problem concerning ocean acidification caused by the increase of atmospheric carbon dioxide started to throw its shadow against aquatic productions including aquaculture. In the present research I clarified what kind of research would be necessary for the stable development of world aquaculture. 2011年度～2014年度科学研究費補助金(基盤研究(C))研究成果報告書 23510044 research report